Hubungan Antara Pembelajaran PAI & Budi Pekerti terhadap Perilaku Sosial Siswa di Sekolah Menengah Pertama: Studi Deskriptif di kelas IX SMPN 48 Bandung - Muhsin; Alifa Fitra Rosiana Azizah; Muhammad Zaenal Asiqin; Rufaidah Azzahra; Suci Rahmad Yani (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This research aims to explore the relationship between learning Islamic Religious Education (PAI) and character towards the social behavior of students in class IX SMPN 48 Bandung. The research method used is qualitative with a naturalistic approach. Data was obtained from students, PAI teachers, school principals, and deputy heads of curriculum. The research results show that PAI learning plays an important role in shaping students' character, especially in the aspect of discipline in worship. Factors such as the behavior and characteristics of other people, cognitive processes, environmental factors, and cultural background also influence students' social behavior. PAI teachers have a crucial role in guiding students to develop positive attitudes, such as a sense of empathy, integrity, responsibility and honesty. There is a positive relationship between PAI learning and students' social behavior, where understanding religious values ​​can influence student behavior positively. PAI teachers also play an important role in shaping students' social behavior through real examples in everyday life and interactive teaching methods. The implications of this research for education are the importance of developing an innovative PAI curriculum, continuous training for PAI teachers, supporting a positive school environment, and involving parents in their children's religious education. It is hoped that the results of this research can contribute to the formation of character and social behavior of students at SMPN 48 Bandung and strengthen understanding of religious values ​​in education.